The relevance of the controller in the strategic planning of a company (Research, Society and Development, 2022)
The controller is responsible for providing the organization's economic, financial and managerial information in the area of controllership. In addition to mastering these areas, it is necessary to be aware of the external changes that the organization may undergo, in order to ensure that the information is timely and relevant, still able to visualize the possible markets in which the organization is located at risk. The general objective of this work is to analyze the relevance of the controller in the strategic planning of a company. The methodology of the work is a bibliographical research, the following databases were accessed: Scientific Electronic Library Online (SCIELO); CAPES Periodicals Portal, UFAM/UEA Repository and Google Schoolar. The controller's role is important to support and guide decision-making, and he or she helps the company to find new alternatives that can positively impact the results. In terms of evaluating results, the controller's contribution is essential, he has a broader view, because he is qualified, due to his professionalism, the controller must make many contributions to the management of the company. In view of all the exposures, it is concluded that a company that employs the controller in its management process is beneficial in the evaluation of its economic results to achieve its objectives and guarantee the company's perpetuity in the market.